Our savage art : poetry and the civil tongue - Logan, William, 1950 November 16- (Columbia University Press, 2009)
The most notorious poet-critic of his generation, William Logan has defined our view of poets good and bad, interesting and banal, for more than three decades. Featured in the New York Times Book Review, the Times Literary Supplement, and the New Criterion, among other journals, Logan's eloquent, passionate prose never fails to provoke readers and poets, reminding us of the value and vitality of the critic's savage art. Like The Undiscovered Country: Poetry in the Age of Tin, which won the National Book Critics Circle Award in Criticism, Our Savage Art features the corrosive wit an.